Synthesis and characterization of zirconia toughened alumina ceramics prepared by co-precipitation method - Rao P.K.; Jana P.; Ahmad M.I.; Roy P.K. (My University, 2025)
Undoped and 3 mol% yttrium doped ZrO2–Al2O3 composite powders with partially stabilized ZrO2 (PSZ) content varying from 0 to 30 wt% were prepared by a co-precipitation route using inorganic precursors Al(NO3)3, ZrOCl2 and Y(NO3)3. The precipitates were characterized by DTA and subsequently calcined at 1200 °C for 4 h to achieve fine grained composite powders. The calcined powders were characterized by FTIR and XRD. In order to enhance the sinterability, the calcined powders were wet milled in a high energy ball mill. Powders were uniaxially pressed to form pellets and sintered at 1600 °C for 5 h to achieve greater than 96% relative density. Microstructural analysis of the sintered compacts revealed the uniform distribution of the zirconia particles among the alumina matrix. It was also observed that the faceted intergranular zirconia grains were present at the grain boundaries and junctions in the alumina matrix. Vickers indentation was carried out at 1 kgf load for hardness and 2 kgf load for estimating the critical stress concentration factor (Kc). Microscopic studies of the indented samples showed that cracks were propagating around the grain boundaries. Highest Kc ∼8.40 ± 0.4 MPa√m and hardness ∼16.31 ± 0.58 GPa was obtained for the 30 wt% PSZ-Al2O3 composite. The sintered density and critical stress intensity factor (Kc) achieved were compararble to that achieved earlier by hot press and SPS. © 2019